Analyses of the genomes, transcriptomes and phenotypic characterization of Salmonella Typhimurium strains isolated from humans, food and swine in Brazil - Seribelli, Amanda Aparecida (2021)
Salmonella enterica subsp. enterica serovar Typhimurium (S. Typhimurium) has been an important cause of gastroenteritis in various countries worldwide. In addition, S. Typhimurium sequence type (ST) 313 has been emerging as a cause of invasive disease mainly in sub-Saharan Africa and its presence was recently described in Brazil. However, in Brazil there are few studies that have elucidated possible differences in the genotypic diversity, gene expression and virulence of S. Typhimurium strains isolated from different sources and belonging to important STs. In the present thesis, six important questions were addressed: (1) What is the diversity of single nucleotide polymorphism (SNP) and resistance genes among S. Typhimurium strains isolated from humans and food? (2) Are genetically distinct the S. Typhimurium ST313 strains isolated from humans and food among each other and in comparison to other STs? (3) How do S. Typhimurium strains isolated from humans and food behave in phenotypic tests related to virulence? (4) What is the genetic diversity of S. Typhimurium strains isolated from swine? (5) What are the genomic differences of S. Typhimurium strains isolated from humans, food and swine? (6) How do the S. Typhimurium ST313 strain behave in a classic animal model and what are their differences in gene expression in comparison to ST19 strains? Phylogenetic results placed the S. Typhimurium strains into two major clades suggesting the existence of a prevalent subtype, likely more adapted, among strains isolated from humans, with some diversity in subtypes in isolates from food. The variety and prevalence of resistant genes found in these Salmonella Typhimurium strains reinforced their potential hazard for humans under treatment and the risk of its presence in foods in Brazil. The ST313 genomes from Brazil showed a high similarity among them which information might eventually help in the development of vaccines and antibiotics. The pangenome analysis showed that the S. Typhimurium genomes studied presented an open pangenome, but specifically tending to become closed for the ST313 strains. The ability of the studied S. Typhimurium to invade Caco-2 epithelial cells was strain dependent and was not related to the source or the year of isolation. However, S. Typhimurium strains isolated from humans showed greater survival rates in U937 human macrophages and presented higher proportion of isolates with a virulent related profile in G. mellonella larvae in comparison to strains isolated from food suggesting that this difference may be related to the higher frequency of human isolates which contained plasmidial genes, such as spvABCDR operon, pefABCD operon, rck and mig-5. The cgMLST and BLAST Atlas were more efficient at discriminating the swine isolates studied in comparison to wgMLST. The pathogenic potential of the swine strains studied was corroborated by the presence of important Salmonella pathogenicity islands (SPIs) related to the pathogenesis of S. Typhimurium. Phylogenetic analyses grouped the majority of the S. Typhimurium strains of diverse origins into a single cluster suggesting that there was one prevalent subtype that has successful contaminated human, food and animal sources for 30 years in Brazil. The orthologous protein clusters analysis revealed unique genes in the S. Typhimurium studied mainly related to bacterial metabolism and that may be important in their pathogenicity. S. Typhimurium isolates from swine showed greater diversity of STs and prophages in comparison to S. Typhimurium strains isolated from humans and foods. The pathogenic potential of S. Typhimurium strains was corroborated by the presence of exclusive prophages of this serovar involved in its virulence. The high number of resistance genes related to efflux pumps is worrying and may lead to therapeutic failures when treatment is needed. S. Typhimurium STm30 (ST313) isolated from human feces in Brazil demonstrated greater expression of genes related to pathogenesis at 37°C, besides better colonization and invasion in the murine colon due to higher levels of expression of virulence genes and pro-inflammatory cytokines were also more expressed in this organ, suggesting greater tissue damage in comparison to S. Typhimurium SL1344 (ST19) and S. Typhimurium STm11 (ST19) isolated from human feces in Brazil. Finally, the results obtained contributed for a better characterization of the virulence and genotypic diversity of this important enteropathogen worldwide.